Thixomolding of magnesium alloy for engineering applications part II [compact disc] : (corrosion and oxidation performance) - 198648 Fadlina Mat Noor (Skudai : Universiti Teknologi Malaysia, 2006)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006